2006
DOI: 10.1207/s15374424jccp3502_17
|View full text |Cite
|
Sign up to set email alerts
|

Trait Affectivity and Nonreferred Adolescent Conduct Problems

Abstract: This study examined for profiles of positive trait affectivity (PA) and negative trait affectivity (NA) associated with adolescent conduct problems. Prior trait affectivity research has been relatively biased toward the assessment of adults and internalizing symptomatology. Consistent with recent developmental modeling of antisocial behavior, this study proposed that conduct problems are uniquely associated with 2 PA-NA profiles (i.e., high PA-high NA and low PA-low NA). A non-referred sample of 109 adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
2
19
0
1
Order By: Relevance
“…Indeed, we found an effect of NE 9 PE along with the separate effects of both NE and PE: low PE seems to be a vulnerability factor in the negative relationship between NE and depressive symptoms. This is consistent with previous findings (e.g., Joiner and Lonigan 2000;Loney et al 2006;Vasey et al 2013a, b;Verstraeten et al 2012;Wetter and Hankin 2009) showing that low levels of PE moderate the relationship between high levels of NE and depressive symptoms in youth. Overall, these findings underscore the importance of including also PE when considering risk and vulnerability factors for depression (Jylhä and Isometsä 2006).…”
Section: Linking Temperamental Reactivity To Depressive Symptoms In Ysupporting
confidence: 93%
See 2 more Smart Citations
“…Indeed, we found an effect of NE 9 PE along with the separate effects of both NE and PE: low PE seems to be a vulnerability factor in the negative relationship between NE and depressive symptoms. This is consistent with previous findings (e.g., Joiner and Lonigan 2000;Loney et al 2006;Vasey et al 2013a, b;Verstraeten et al 2012;Wetter and Hankin 2009) showing that low levels of PE moderate the relationship between high levels of NE and depressive symptoms in youth. Overall, these findings underscore the importance of including also PE when considering risk and vulnerability factors for depression (Jylhä and Isometsä 2006).…”
Section: Linking Temperamental Reactivity To Depressive Symptoms In Ysupporting
confidence: 93%
“…Current evidence of research investigating the NE 9 PE interaction indicates that low PE indeed acts as a vulnerability factor (i.e., moderator) in the association between high levels of NE and depressive symptoms. This has been found in non-clinical youth (Loney et al 2006;Vasey et al 2013a, b), as well as in youth psychiatric inpatients (Joiner and Lonigan 2000). Additionally, a handful of studies also found prospective evidence for high PE as a resilience factor, buffering the effect of high levels of NE on depressive symptoms (Vasey et al 2013a, b;Wetter and Hankin 2009).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…For example, Joiner and Lonigan (2000) found a significant NA Â PA interaction such that high NA was associated with a concurrent diagnosis of depression and an increase in depressive symptoms across two months when PA was low, but not when it was high. This interaction has been replicated in non-clinical youth samples both concurrently (Loney, Lima, & Butler, 2006) and prospectively (Vasey, Harbaugh, Mikolich, Firestone, & Bijttebier, 2013;Wetter & Hankin, 2009; though see Verstraeten et al, 2009). Studies including analogous interactions involving N, E, BIS sensitivity, and BAS sensitivity have produced similar results in both youth and adult samples (e.g., Gershuny & Sher, 1998;Knyazev & Wilson, 2004;McFatter, 1994), though a few studies have failed to find the effect (e.g., Jorm et al, 2000).…”
Section: Introductionmentioning
confidence: 85%
“…The paucity of results in this field might stem from the counter-intuitive nature of the relationship between anxiety and antisocial behavior. Many psychophysiological studies have shown that low levels of anxiety are closely connected to antisocial, aggressive, or delinquent behavior (for a review, see Scarpa and Raine 2004;Herpertz et al 2001Herpertz et al , 2005, and low levels of anxiety are associated with an increased risk for ongoing antisocial behavior (Loney et al 2006;Herpertz et al 2003;Moffitt et al 2002). Furthermore, there is growing evidence that low anxiety in some children is closely connected with callous-unemotional traits that are observed in children with a particularly severe, aggressive, and stable pattern of antisocial behavior (for a review, see Frick 2009).…”
Section: Introductionmentioning
confidence: 99%